Hubungan Kebersyukuran dengan Perilaku Prososial pada Anggota IPNU-IPPNU - Zulkarnain, Muhammad Rizki; Maryam, Effy Wardati (Academicia Globe: Inderscience Research, 2020)
This study was motivated by the phenomenon of social behavior problems among IPNU-IPPNU members in the village of Candipari. It can be seen from the interview results that the problems faced by the members show a lack of pro-social behavior. This can be seen from the lack of cooperation among members, honesty and mutual help as aspects of social behavior. This study aims to understand the relationship between gratitude and pro-social behavior between IPNU and IPPNU members in Candipari village. The students in this study are members of IPNU and IPPNU in the village of Candipari. The sampling method in this study is used for saturation sampling. The research method used is quantitative research using an interactive approach. The data collection method used psychological scales, namely affective behavior scale and gratitude scale. The construction of the psychological scale in this study uses the Likert scale model (response scale). The data analysis method used in this study is the Pearson correlation method (Product Moment) using the software SPSS 20 for windows. Based on the analysis results, the data analysis test results obtained a correlation coefficient of 0.640 with a significance level of 0.000 < 0.05. This means that there is a strong relationship between gratitude and pro-social behaviour. Based on the experimental results, the coefficient of determination for the result is 0.395 (R Square), which means that in this study the gratitude variable contributes 39.5% to the affective behavioral variable. Based on the experimental results, the proposed hypothesis is acceptable, that is, there is a positive relationship between Gratitude and social behavior of IPNU-IPPNU members in Candipari village.